2007
DOI: 10.1093/jxb/erl248
|View full text |Cite
|
Sign up to set email alerts
|

Unique properties of NADP-thioredoxin reductase C in legumes

Abstract: NADP-thioredoxin reductases (NTRs) reduce thioredoxins (Trxs), using NADPH as a reductant, together constituting complete redox systems (NTS). Beside NTRA and NTRB targeted to both cytosol and mitochondria of plant cells, there is in chloroplasts an unusual NTR (NTRC) harbouring a Trx domain in a C-terminal extension, as recently reported in Oryza sativa. Although NTRC may constitute a complete NTS, it was described as a bifunctional enzyme. Because the gene is only present in photosynthetic organisms and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 33 publications
1
62
0
Order By: Relevance
“…Moreover, the analysis of these plants revealed a more unexpected expression in tissues of reproductive organs, such as stigma and anthers. Therefore, although NTRC is expressed at high levels in photosynthetic tissues, in agreement with previous reports (Serrato et al, 2004;Moon et al, 2006;Alkhalfioui et al, 2007;Lepistö et al, 2009), the different approaches performed in this work reveal a broad pattern of expression in either photosynthetic and nonphotosynthetic tissues for this gene.…”
Section: Ntrc Is Important For Redox Homeostasis Of Plastids Of Photosupporting
confidence: 91%
“…Moreover, the analysis of these plants revealed a more unexpected expression in tissues of reproductive organs, such as stigma and anthers. Therefore, although NTRC is expressed at high levels in photosynthetic tissues, in agreement with previous reports (Serrato et al, 2004;Moon et al, 2006;Alkhalfioui et al, 2007;Lepistö et al, 2009), the different approaches performed in this work reveal a broad pattern of expression in either photosynthetic and nonphotosynthetic tissues for this gene.…”
Section: Ntrc Is Important For Redox Homeostasis Of Plastids Of Photosupporting
confidence: 91%
“…M. truncatula NTRA (MtNTRA; Alkhalfioui et al, 2007) was chosen for these experiments, because it had previously been shown that NTRs of the A/B Figure 1. Darwin tree of M. truncatula and Arabidopsis Trx protein sequences.…”
Section: Typesmentioning
confidence: 99%
“…Trx activity was measured using the insulin or DTNB reduction assays as previously described (Holmgren, 1979;Jacquot et al, 1995) using either DTT or NADPH plus recombinant MtNTRA (Alkhalfioui et al, 2007) as a reductant.…”
Section: Enzymatic Assaysmentioning
confidence: 99%
“…NTRC is exclusive of organisms that perform oxygenic photosynthesis and shows plastid localization in plants (Kirchsteiger et al, 2012). Moreover, biochemical analyses revealed that NTRC is able to conjugate both NTR and Trx activities to efficiently reduce the hydrogen peroxide-scavenging enzyme 2-Cys peroxiredoxin (Moon et al, 2006;Pérez-Ruiz et al, 2006;Alkhalfioui et al, 2007). Arabidopsis (Arabidopsis thaliana) NTRC knockout mutants show a characteristic phenotype of retarded growth and pale green leaves, this phenotype being more severe under shortday conditions (Pérez-Ruiz et al, 2006;Lepistö et al, 2009).…”
mentioning
confidence: 99%